Verbandliche Interessenvertretung und Kooperationspotenziale auf dem migrantischen Organisationsfeld in NRW - Halm, Dirk; Söylemez, Seckin (2023)
The field of migrant organisations in North Rhine-Westphalia (NRW) is highly fragmented due to various waves of migration, origin groups, intergenerational changes and the reproduction of ideological, political and religious diversity in the countries of origin. Nevertheless, there are numerous associations representing migrants’ interests that encompass migrant organisations. This study is the first to provide an overview of migration-related associational organisations in NRW, upon which modelling of migration-related political representation is based and through which an assessment of opportunities for cooperation and prospects for funding can be made.